Glutathion-S- transferase Enzyme and Malondialdehyde (MDA) in Colorectal Cancer and in Healthy Control - Mahmood, Noah A (Iraqi Journal of Cancer and Medical Genetics, 2010)
Oxidative stress is closely related to all aspects of cancer, from carcinogenesis to the tumor-bearing state, from treatment to prevention. The human body is constantly under oxidative stress arising from exogenous origins (e.g., ultraviolet rays) and endogenous origins (at the cellular level where mitochondria are involved). When such oxidative stress exceeds the capacity of the oxidation-reduction system of the body, gene mutations may result or intracellular signal transduction and transcription factors may be affected directly or via antioxidants, leading to carcinogenesis. Aim: The study focuses on the plasma Glutathion S-transferase (GST) level, Malondialdehyde (MDA) level in colorectal cancer patient which result due to an imbalance between aggressive and defensive factors. Materials and Methods: the study included 40 patient and 20 healthy individuals for comparative analysis were considered for the present study. Serum (GST) and (MDA) levels of each individual were performed. Results: Statistical analysis of serum antioxidant enzymes level and antioxidant status revealed a significant increase in malondialdehyde (MDA) (p< 0.001 respectively. The total plasma GST exhibited nearly a 2–3- fold increase (p < 0.001) in the patient plasma samples as compared with the corresponding controls. The increasing preponderance of plasma MDA and GST enzyme level can be explained on the basis of alteration of enzymes activity, which may lead to disturbance in homeostasis of antioxidant/oxidant balance